Spliceosomal protein eftud2 mutation leads to p53-dependent apoptosis in zebrafish neural progenitors - Lei, Lei; Yan, Shou-Yu; Yang, Ran; Chen, Jia-Yu; Li, Yumei; Bu, Ye; Chang, Nannan; Zhou, Qinchao; Zhu, Xiaojun; Li, Chuan-Yun; Xiong, Jing-Wei (Nucleic acids research, 2017)
Haploinsufficiency of EFTUD2 (Elongation Factor Tu GTP Binding Domain Containing 2) is linked to human mandibulofacial dysostosis, Guion-Almeida type (MFDGA), but the underlying cellular and molecular mechanisms remain to be addressed. We report here the isolation, cloning and functional analysis of the mutated eftud2 (snu114) in a novel neuronal mutant fn10a in zebrafish. This mutant displayed abnormal brain development with evident neuronal apoptosis while the development of other organs appeared less affected. Positional cloning revealed a nonsense mutation such that the mutant eftud2 mRNA encoded a truncated Eftud2 protein and was subjected to nonsense-mediated decay. Disruption of eftud2 led to increased apoptosis and mitosis of neural progenitors while it had little effect on differentiated neurons. Further RNA-seq and functional analyses revealed a transcriptome-wide RNA splicing deficiency and a large amount of intron-retaining and exon-skipping transcripts, which resulted in inadequate nonsense-mediated RNA decay and activation of the p53 pathway in fn10a mutants. Therefore, our study has established that eftud2 functions in RNA splicing during neural development and provides a suitable zebrafish model for studying the molecular pathology of the neurological disease MFDGA.